2014
DOI: 10.1161/hypertensionaha.114.04282
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-to-Measurement Blood Pressure Variability Is Related to Cognitive Performance

Abstract: The objective was to investigate the association between variability in blood pressure and cognitive function for sitting, standing and reclining blood pressure values, and variability derived from all 15 measures. In previous studies only sitting blood pressure values have been examined, and only a few cognitive measures have been employed. A secondary objective was to examine associations between blood pressure variability and cognitive performance in hypertensive individuals stratified by treatment success.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
(69 reference statements)
4
27
1
Order By: Relevance
“…Recent studies also suggest that increased BP variability is associated with poorer cognitive performance and worsening psychomotor speed and verbal memory [7,36]. Stabouli et al showed that increased SBP variability is closely associated with arterial stiffness (assessed by pulse wave velocity) in children and adolescents [37], which would suggest that increased BP variability may precede early vascular damage/ early onset of atherosclerosis.…”
Section: Bp Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also suggest that increased BP variability is associated with poorer cognitive performance and worsening psychomotor speed and verbal memory [7,36]. Stabouli et al showed that increased SBP variability is closely associated with arterial stiffness (assessed by pulse wave velocity) in children and adolescents [37], which would suggest that increased BP variability may precede early vascular damage/ early onset of atherosclerosis.…”
Section: Bp Variabilitymentioning
confidence: 99%
“…Several recent studies in adult patients have demonstrated that an increased BP variability (short-term and/or long-term) also has a significant impact on TOD [3], cardiovascular morbidity [4], progression of kidney disease [5,6] and cognitive function [7,8], independent of the BP level.…”
Section: Introductionmentioning
confidence: 99%
“…Health care clinics often use blood pressure (BP) measurements to assess patients’ risk for cardiovascular problems (Crichton et al, 2014). Patients with hypertension are at particular risk for stroke, vascular dementia, and Alzheimer disease (Peila et al, 2006; Posner et al, 2002).…”
mentioning
confidence: 99%
“…In recent years, greater variability in BP measurements (ie, changes in BP at different time points) has been linked to a higher risk for stroke and other cardiovascular events (Floras, 2013; Rothwell, 2010; Rothwell et al, 2010). Because wide BP variability is found in patients with brain structure abnormalities (Gunstad et al, 2009; Nagai et al, 2011; Sabayan et al, 2013) or hypertensive cardiovascular complications (Kanemaru et al, 2001), Crichton et al (2014) suggested that BP variability also affects cognitive performance.…”
mentioning
confidence: 99%
“…Also, we did not assess other cognitive outcomes which might be impacted by BP lowering drugs 35 and BPV. 36 Finally, although we adjusted for comorbidities and discerned drug use for hypertension from other uses, we cannot rule out indication biases. For example, it is possible that β-blockers were favored by prescribers for their cardiovascular benefits in patients with coronary disease and acute cardiovascular event history.…”
Section: -25mentioning
confidence: 99%